Building for the Future 2017 Annual Report - Floros, John D. (My University, 2017)
This informal report to the Kansas Legislature summarizes the wide-ranging impact of K-State Research and Extension in 2017, highlighting initiatives in agriculture, environmental stewardship, public health, and community development across Kansas.
UNN31_2017_01
Keywords: UNN31; Administrative and Research Reports; legislature